Outpatient visits and treatment methods of patients with hand and wrist injuries in Vreden National Medical Research Center of Traumatology and Orthopedics - Eugeniy V. Veber; Alexander P. Zavyalov; Alexander I. Avdeev; Margarita A. Zhogina; Sergey S. Smirnov (Travmatologiâ i Ortopediâ Rossii)
Background. Number of injuries of the hand and wrist is constantly growing from year to year. Inpatient treatment of these patients increases both time and financial costs for healthcare organizations. Thus, analysing the structure of patients who applied to the emergency department would make it possible to take more objective decisions on the organization of healthcare delivery.